Infectivity and pathogenicity of different hepatitis E virus genotypes/subtypes in rabbit model. Issue 1 (1st January 2020) - Li, Shuangshuang; He, Qiyu; Yan, Li; Li, Manyu; Liang, Zhaochao; Shu, Jingyi; Zhang, Fan; Wang, Ling; Wang, Lin
ABSTRACT: The pathogenicity of each hepatitis E virus (HEV) genotypes/subtypes may be different. This study aimed to investigate the infectivity and pathogenicity of different HEV genotypes/subtypes from different mammalian sources especially human in rabbits, and to assess whether rabbits are an appropriate animal model to study different HEV genotypes/subtypes. Thirty-seven rabbits were randomly divided into nine groups and inoculated with eight different HEV strains, including human-derived HEV3b (hHEV-3b), hHEV-4a, hHEV-4d and hHEV-4h, swine-derived HEV4d (sHEV-4d) and sHEV-4h, rabbit-derived HEV3 (HEV-3ra) and camel-derived HEV8. HEV RNA, antigen, anti-HEV and alanine aminotransferase (ALT) in serum or/and feces were monitored weekly. One rabbit from each group was euthanized at seven weeks post inoculation and the liver specimens were taken for histopathological analysis and immunofluorescence staining of HEV ORF2 proteins. hHEV-4d, sHEV-4d and HEV-3ra infections were successfully established in rabbits and typical acute hepatitis symptoms were observed, including viraemia/antigenemia, fecal virus/antigen shedding, elevated ALT level and liver histopathological changes. One rabbit infected with HEV-3ra showed chronic infection. hHEV-4d and sHEV-4d are less infectious and pathogenic than HEV-3ra in rabbits. hHEV-3b and HEV8 only caused inapparent infection in rabbits as 60% (3/5) and 20% (1/5) of the rabbits seroconverted to anti-HEV, respectively. No obvious signs of HEV infection in rabbits inoculated with hHEV-4a, hHEV-4h and sHEV-4h. The infectivity and pathogenicity of different HEV genotypes/subtypes in rabbits is different, which may be related to the species specificity of HEV. Rabbit can be used as an animal model for the study of HEV-3ra and more importantly human HEV-4d.